2000
DOI: 10.1097/00005650-200005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Effectiveness of a Brief Smoking-Cessation Intervention for Hospital Patients

Abstract: We recommend implementation of hospital-based smoking-cessation counseling by professional counselors whose primary responsibility is to deliver the intervention. Recommendations for future research and for innovative ways to reach hospitalized smokers who are not receiving intervention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…We also found a higher odds of treatment among patients who received nurse-delivered predischarge counseling. Although there is concern about the effectiveness of this low-intensity counseling intervention alone to produce sustained quit rates, 27,28 an associated increase in the use of pharmacotherapy for tobacco cessation may prove to be effective, and is supported by our results. Pairing this nurse-based intervention with other processes that facilitate treatment, such as changes to electronic discharge order sets, may further improve the use of medications.…”
Section: Discussionsupporting
confidence: 67%
“…We also found a higher odds of treatment among patients who received nurse-delivered predischarge counseling. Although there is concern about the effectiveness of this low-intensity counseling intervention alone to produce sustained quit rates, 27,28 an associated increase in the use of pharmacotherapy for tobacco cessation may prove to be effective, and is supported by our results. Pairing this nurse-based intervention with other processes that facilitate treatment, such as changes to electronic discharge order sets, may further improve the use of medications.…”
Section: Discussionsupporting
confidence: 67%
“…Canga et al found it possible for a single nurse to provide services to a wide variety of primary care and hospital practices. This is consistent with the results of a recently reported hospital-based smoking cessation program (9), which found smoking cessation to be more effective when delivered by trained experienced smoking counselors rather than when delivered by respiratory therapists who had many other responsibilities. It would be informative to know more about how Canga et al handled the linkage to primary care, kept the practices informed, and used them to reinforce patient success.…”
supporting
confidence: 90%
“…For example, a meta-analysis of multisystemic therapy for adolescent conduct disorder reported that effect sizes achieved in community effectiveness studies were less than one-third of those reported in university-based efficacy studies. 53,54 In some cases, interventions that appear clearly efficacious may be ineffective in a community setting, 55 although equivalent outcomes may also sometimes be reported. 56 The generally accepted 'technology model' of psychotherapy research 57,58 involves three elements: specification of treatments in manuals, training and supervision of therapists to ensure that treatment is delivered as uniformly as possible, and monitoring of treatment delivery.…”
Section: Fidelity Of the Interventionmentioning
confidence: 99%